Future Heat Stress During Muslim Pilgrimage (Hajj) Projected to Exceed “Extreme Danger” Levels - Suchul Kang; Jeremy S. Pal; Elfatih A.B. Eltahir (Geophysical Research Letters)
Abstract The Muslim pilgrimage or Hajj, which is one of the five pillars of Muslim faith, takes place outdoors in and surrounding Mecca in the Saudi Arabian desert. The U.S. National Weather Service defines an extreme danger heat stress threshold which is approximately equivalent to a wet‐bulb temperature of about 29.1 °C—a combined measure of temperature and humidity. Here, based on results of simulations using an ensemble of coupled atmosphere‐ocean global climate models, we project that future climate change with and without mitigation will elevate heat stress to levels that exceed this extreme danger threshold through 2020 and during the periods of 2047 to 2052 and 2079 to 2086, with increasing frequency and intensity as the century progresses. If climate change proceeds on the current trajectory or even on a trajectory with considerable mitigation, aggressive adaptation measures will be required during years of high heat stress risk.